2023
DOI: 10.1093/europace/euac246
|View full text |Cite
|
Sign up to set email alerts
|

360° Virtual reality to improve patient education and reduce anxiety towards atrial fibrillation ablation

Abstract: Aims Evaluation of (i) the effects of a virtual reality (VR) preprocedural patient education video on information provision, procedure-related knowledge, satisfaction, and the level of worries in patients planned for atrial fibrillation (AF) ablation and (ii) the feasibility of a disposable cardboard VR viewer for home use in this setting. Methods and results In this prospective observational cohort study, patients were alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…This research highlighted that combining VR with 3D printed models for patient education not only elevated patient satisfaction but also effectively alleviated preoperative anxiety. Furthermore, a separate study indicated that VR educational videos, when offered to patients awaiting atrial fibrillation ablation, enhanced the quality of information provided, deepened procedural understanding, boosted patient satisfaction, and reduced procedural anxiety 14 . Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…This research highlighted that combining VR with 3D printed models for patient education not only elevated patient satisfaction but also effectively alleviated preoperative anxiety. Furthermore, a separate study indicated that VR educational videos, when offered to patients awaiting atrial fibrillation ablation, enhanced the quality of information provided, deepened procedural understanding, boosted patient satisfaction, and reduced procedural anxiety 14 . Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“… 12 Recently, modern technological solutions, such as virtual reality videos, have been shown to provide better information and reduce anxiety in patients submitted to atrial fibrillation ablation. 13 Similar technologies could be adapted to ICD patients.…”
Section: Discussionmentioning
confidence: 99%
“…VR patient education is commonly a 360° video of the procedure enhancing patients’ knowledge of the procedure and managing (negative) expectations. 12 However, similar to preprocedural educational videos, only virtual experience of the procedure prior may not be sufficient in reducing anxiety, pain and stress. VRD and VRH are primarily developed to reduce anxiety, pain and stress.…”
Section: Introductionmentioning
confidence: 99%